Odpowiedzi

2010-03-11T23:23:16+01:00
A) 2(x + 3) =10
2x+6=10
2x=10-6
2x=4
x=2

b) 3(x - 1)+2 = 8
3x-3+2=8
3x=8+1
3x=9
x=3

c) 2( 13 - x )-9 = 1
26-2x-9=1
-2x=1-26+9
-2x=-16
x=8

d) 3(1 - x) + 2 = -7
3-3x+2=-7
-3x=-7-3-2
-3x=-12
x=4

f) 4(3x + 2) + 5 (2x + 3)= -(2x + 13)
12x+8+10x+15=-2x-13
22x+2x=-13-8-15
24x=-36
x=-1,5

h) 2(x - 4)= 2(2x-1) + 6 ( x +1)
2x-8=4x-2+6x+6
2x-10x=4+8
-8x=12
x=-1,5
49 4 49
2010-03-11T23:30:31+01:00
A) 2x+6=10
2x=4/2
x=2
b] 3x-3+2=8
3x=8+3-2
3x=9/3
x=3
c}
26-2x-9=1
-2x=1+9-26
-2x=-16/-2
x=8
d}
3-3x+2=-7
-3x=-7-2-3
-3x=-12/-3
x=4
f}
12x+8+10x+15=-2x-13
12x+1*x+2x=-13-8-15
24x=-36/24
x=-9/6=-1,5
h}
2x-8=4x-2+6x+6
2x-4x-6x=-2+6+8
-8x=12/8
x=-1,5
20 3 20
2010-03-11T23:38:25+01:00
A.2(x+3)=10
2x+6=10
2x=-6+10
2x=4÷2
x=2
b.3(x-1)+2=8
3x-3+2=8
3x=3-2+8
3x=9÷3
x=3
c.2(13-x)-9=1
26-2x-9=1
2x=-26+9+1
2x=-16÷2
x=8
d.3(1-x)+2=-7
3-3x+2=-7
3x=-3-2-7
3x=-12÷3
x=4
f.4(3x+2)+5(2x+3)=-(2x+13)
12x+8+10x+15=-2x-13
12x+10x+2x=-8-15-13
24x=-36÷24
x=-36/24
x=-6/4
x=-1,5
h.2(x-4)=2(2x-1)+6(x+1)
2x-8=4x-2+6x+6
2x-4x-6x=8-2+6
-8x=12÷(-8)
x=-12/8
x=-1,5

h.
17 2 17